Morphological differences between putative Paleolithic dogs and wolves: A commentary to Janssens et al. (2021). Issue 12 (26th April 2022) - Galeta, Patrik; Lázničková‐Galetová, Martina; Sablin, Mikhail; Germonpré, Mietje
Abstract: Janssens et al. (2021, doi: 10.1002/ar.24624) recently commented on our article (Galeta et al., 2021, doi: 10.1002/ar.24500) regarding the morphological differences between putative Paleolithic dog and Pleistocene wolf crania. The authors argued that these differences reflect the normal population variation of wolves, that some of the cranial measurements used do not reflect morphological changes during domestication, and that our canid dataset was small because we inexplicably omitted several specimens we analyzed in our previous publications. In this commentary, we briefly address the issue of within and between morpho‐population variability. The results based on our canid sample suggest that the magnitude of morphological differences between distinct morpho‐populations (i.e., recent northern dogs and wolves) is at least twice as large as that observed within morpho‐populations (between two groups of recent northern wolves segregated by cluster analysis). The morphological differences between putative Paleolithic dogs and Pleistocene wolves are relatively large, which may indicate that they did not likely represent a single Late Pleistocene morpho‐population. Finally, we clarified the rationale behind the composition of our 2021 dataset to show that we did not adjust the list of the analyzed specimens. Although the sample size was small, the randomization analysis published in 2021 confirmed that the unbalanced composition of the reference sample did not affect the reliability of the morphological segregation of putative Paleolithic dogs and Pleistocene wolves.